A National Description of Violence toward Emergency Medical Services Personnel. (3rd July 2016) - Gormley, Mirinda A.; Crowe, Remle P.; Bentley, Melissa A.; Levine, Roger
Abstract: Introduction: EMS personnel often work in unpredictable environments and are at high risk for sustaining occupational injuries. One potential source of injury that is of growing concern is violence toward EMS personnel.Objective: To describe the prevalence of violence directed at EMS personnel by type and source, and to identify characteristics associated with experiencing violence.Methods: The 2013 Longitudinal EMT Attributes and Demographics Study contained 14 items assessing violence experienced in the past 12 months. Violence was categorized by type (physical or verbal) and by source (the patient or a patient's family member or bystander). EMS personnel characteristics included sex, age, race, marital status, certification level, firefighter, volunteerism, agency type, and community size. Descriptive and comparative analyses were performed on personnel whose primary role was providing patient care. Multivariable logistic regression modelling was used to assess associations between provider characteristics and experiencing violence.Results: A total of 2, 515/4, 238 (59.3%) responses were received and 1, 789 met inclusion criteria. Over two-thirds (69.0%) experienced at least one form of violence in the past 12 months. Verbal violence was more prevalent than physical (67.0% vs. 43.6%). Using multivariable logistic regression to control for other demographic and employment characteristics, paramedics had nearly triple the odds of experiencing physical (OR = 2.67, 95% CI = 2.06–3.46) and verbal (OR = 2.63, 95% CI = 1.99–3.46) violence as EMTs. Urban personnel had increased odds of experiencing physical (OR = 1.53, 95% CI = 1.21–1.93) and verbal violence (OR = 1.32, 95% CI = 1.02–1.71). Each additional weekly transport increased the odds of experiencing physical (OR = 1.04, 95% CI = 1.03–1.05) and verbal (OR = 1.04, 95% CI = 1.03–1.06) violence by 4%. Those who were volunteers at their main EMS jobs had decreased odds of experiencing physical (OR = 0.68, 95% CI = 0.50–0.92) and verbal (OR = 0.59, 95% CI = 0.44–0.78) violence.Conclusions: Over two-thirds of EMS personnel experienced at least one form of violence in the last 12 months. Demographic and employment characteristics associated with experiencing violence were identified. Our findings may be used in education initiatives to raise awareness of the high prevalence of violence toward EMS personnel and factors associated with experiencing violence.